The handbook of technical analysis : - Lim, Mark Andrew (Wiley, 2016)
The book is also an excellent resource for serious traders and technical analysts, and includes a chapter dedicated to advanced money management techniques. This chapter helps complete a student's education and also provides indispensable knowledge for FOREX, bond, stock, futures, CFD, and option traders.